Sperm Separation and Selection Techniques to Mitigate Sperm DNA Damage - Steven Fleming; David Morroll; Martine Nijs (Life)
Semen preparation and sperm selection techniques exploit the morphological and physiological characteristics of sperm function, including motility, morphology, density, and maturity, as reflected by their cell-surface charge and the expression of hyaluronan receptors. The various methods employed have a common purpose of mimicing sperm selection within the female reproductive tract and, thereby, increasing the likelihood that oocytes will be fertilised by spermatozoa with intact nuclear DNA and a normal genome. Indeed, the paternal genome is relevant to embryonic genome activation and blastocyst development, and has a fundamental impact upon successful implantation, ongoing pregnancy and live birth. The clinical use of both well-established and some more recently developed techniques is discussed in this comparative clinical review of sperm separation from seminal plasma and selection for insemination.